Increasing Teacher Capacity Using the Index Card Match Type Active Learning Model Through Continuous Mentoring at SD Negeri 1 Samigaluh, Kapanewon Samigaluh Academic Year 2022/2023 - Sumadi, Sumadi (Universitas Islam Indonesia, 2024)
The School Action Research aims to improve teachers' abilities in using the card match index type learning model through continuous mentoring at SD Negeri 1 Samigaluh for the 2022/2023 school year. This type of school action research is carried out in 2 cycles, where each cycle consists of 2 meetings each. The implementation steps use research methods/procedures, which are carried out based on the planning, implementation, observation and reflection stages. The research subjects were 8 teachers at SD Negeri 1 Samigaluh, Kapanewon Samigaluh, Kulon Progo Regency for the 2022/2023 academic year, consisting of class teachers and mapel teachers. The research object is about using the card match index type learning model. Results of action research on sustainable mentoring schools using the card match index type active learning model. shows that through mentoring it can be proven by increasing observation results at each meeting. The results of the research can be stated that the activeness of mentoring participants in participating in all physical and non-physical activities of participants in the process of mentoring activities is optimal so that it can create a conducive atmosphere and can increase activeness in participating in mentoring using the card match index type active learning model at SD Negeri 1 Samigaluh Kapanewon Samigaluh Kulon Progo Regency.